Endothelial Microparticles From Acute Coronary Syndrome Patients Induce Premature Coronary Artery Endothelial Cell Aging and Thrombogenicity: Role of the Ang II/AT1 Receptor/NADPH Oxidase-Mediated Activation of MAPKs and PI3-Kinase Pathways. Issue 3 (17th January 2017) - Abbas, Malak; Jesel, Laurence; Auger, Cyril; Amoura, Lamia; Messas, Nathan; Manin, Guillaume; Rumig, Cordula; León-González, Antonio J.; Ribeiro, Thais P.; Silva, Grazielle C.; Abou-Merhi, Raghida; Hamade, Eva; et al.
Abstract : Background: Microparticles (MPs) have emerged as a surrogate marker of endothelial dysfunction and cardiovascular risk. This study examined the potential of MPs from senescent endothelial cells (ECs) or from patients with acute coronary syndrome (ACS) to promote premature EC aging and thrombogenicity. Methods: Primary porcine coronary ECs were isolated from the left circumflex coronary artery. MPs were prepared from ECs and venous blood from patients with ACS (n=30) and from healthy volunteers (n=4) by sequential centrifugation. The level of endothelial senescence was assessed as senescence-associated β-galactosidase activity using flow cytometry, oxidative stress using the redox-sensitive probe dihydroethidium, tissue factor activity using an enzymatic Tenase assay, the level of target protein expression by Western blot analysis, platelet aggregation using an aggregometer, and shear stress using a cone-and-plate viscometer. Results: Senescence, as assessed by senescence-associated β-galactosidase activity, was induced by the passaging of porcine coronary artery ECs from passage P1 to P4, and was associated with a progressive shedding of procoagulant MPs. Exposure of P1 ECs to MPs shed from senescent P3 cells or circulating MPs from ACS patients induced increased senescence-associated β-galactosidase activity, oxidative stress, early phosphorylation of mitogen-activated protein kinases and Akt, and upregulation of p53, p21, and p16. Ex vivo, the prosenescent effect of circulating MPs from ACS patients was evidenced only under conditions of low shear stress. Depletion of endothelial-derived MPs from ACS patients reduced the induction of senescence. Prosenescent MPs promoted EC thrombogenicity through tissue factor upregulation, shedding of procoagulant MPs, endothelial nitric oxide synthase downregulation, and reduced nitric oxide–mediated inhibition of platelet aggregation. These MPs exhibited angiotensin-converting enzyme activity and upregulated AT1 receptors and angiotensin-converting enzyme in P1 ECs. Losartan, an AT1 receptor antagonist, and inhibitors of either mitogen-activated protein kinases or phosphoinositide 3-kinase prevented the MP-induced endothelial senescence. Conclusions: These findings indicate that endothelial-derived MPs from ACS patients induce premature endothelial senescence under atheroprone low shear stress and thrombogenicity through angiotensin II–induced redox-sensitive activation of mitogen-activated protein kinases and phosphoinositide 3-kinase/Akt. They further suggest that targeting endothelial-derived MP shedding and their bioactivity may be a promising therapeutic strategy to limit the development of an endothelial dysfunction post-ACS. Abstract : Supplemental Digital Content is available in the text.